An Overview of the Mechanisms of Cadmium-induced Toxicity in the Male Reproductive System - Samar A. Antar; Aymen Halouani; Cherry Gad; Ahmed Ali Al-Karmalawy (Tabriz University of Medical Sciences, 2024)
Cadmium (Cd) is a toxic heavy metal that is known to accumulate in various organs and tissues in the body, including the testes. Exposure to Cd has been shown to cause significant testicular damage, including impaired spermatogenesis and decreased fertility in both humans and animals. This damage is thought to be due to Cd-induced oxidative stress and inflammation, which can lead to cellular damage and apoptosis. Cd has also been shown to disrupt the blood-testis barrier, leading to increased permeability and an altered testicular microenvironment. In addition, Cd exposure has been linked to changes in hormone levels, including decreased testosterone production and altered gonadotropin secretion. Reactive oxygen species (ROS) and an imbalance in the activity of antioxidant enzymes cause oxidative stress. The nuclear factor kappa-B (NF-κB) signaling system, which controls multiple genes involved in inflammatory responses including tumor necrosis factor (TNF-α), is activated by oxidative stress. These effects can contribute to decreased sperm count, motility, and viability. Efforts to reduce exposure to Cd may help to prevent or mitigate the harmful effects on testicular function. This can be achieved through occupational and environmental regulations, as well as public education and awareness programs. In this review, we highlight many of the principal mechanisms included in testicular damage. These pathways could be considered promising targets for the development of potential therapies for a variety of important human diseases.